Petroleum Fiscal Systems, Erik T. Jarlsby and Eduardo G. Pereira (2018). Issue 3 (1st September 2020) - Jiyad, Ahmed Mousa
Review of: Petroleum Fiscal Systems, Erik T. Jarlsby and Eduardo G. Pereira (2018)Oklahoma, OK: PennWell Books, 471 pp., ISBN 978-1-59370-480-3, h/bk, 119